Estudo de viabilidade da aplicação do concreto pré-moldado em reservatórios do sistema de abastecimento de água - Reis, Fabrício André Nogueira dos (Universidade Federal de São Carlos, 2020)
This work aimed to study the economic and financial viability of the application of precast concrete for the construction of circular surface reservoir in urban infrastructure works, considering the current conditions and the premises adopted in the analyzes. In addition, an economic-financial feasibility analysis methodology was presented to assist the decision-making of project managers in choosing the construction system during the preliminary study stage of the project. Using the Equivalent Annual Cost method and sensitivity analysis of indicators with the variation of the input data, the economic indicators were compared between the construction of the prestressed precast concrete reservoir and the construction in cast in place concrete with post prestressing in greased strings and, it was concluded that, under the current market conditions, in many situations the economic and financial results were satisfactory for the precast concrete when it was considered the benefit of anticipating the start of operation of the system water supply, resulting in increases in operating profits in the project's cash flow in relation to the cast in place concrete reservoir. However, there must be a strict planning and control of deadlines and interferences for compatibility of all works that will provide functionality to the water supply system, because when it was not considered to take advantage of the potential of the system's inauguration with the use of precast concrete, there was no situation of economic and financial viability of the use of this construction system in comparison to the use of cast in place concrete, in the current conditions of the Brazilian market. In this research, the impact of the project's useful life, maintenance costs, transport costs, operating profit per residence of the concessionaire company and the anticipation of the start-up time of the water supply system with the use of precast concrete were also evaluated on the economic and financial indicators of the feasibility analysis.
Feasibility study of the application of precast concrete in reservoirs of the water supply system
Keywords: Concreto pré-moldado; Reservatórios circulares; Infraestrutura urbana; Análise de viabilidade; Viabilidade econômico-financeira de projetos; Precast concrete; Circular reservoirs; Urban infrastructure; Feasibility analysis; Economic and financial feasibility of projects.; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL